Solving the Rubik's Cube: understanding the many sides of the municipal stormwater program - DeMasters, Megan M., author; Opp, Susan, advisor; Saunders, Kyle L., committee member; Davis, Sandra, committee member; Carcasson, Martin, committee member (Colorado State University. Libraries, 2017)
The importance of water to support all aspects of human and non-human life has led to debates over the quality of water in the United States and continues to be a salient political issue. Stormwater runoff specifically continues to be a primary source of water pollution in the United States posing risks to human health and ecosystems which is further exacerbated by the impacts of climate change. Growing concerns over water quality due to stormwater runoff as well as mixed results on the effectiveness of the stormwater permitting program is the basis for this research and the questions this dissertation seeks to answer. The purpose of this dissertation is to gain a better understanding of how the municipal stormwater program operates by examining phase II of the program. To accomplish the goals for this dissertation, three separate research articles are presented that each utilize and draw from distinct theories but are, at the same time, connected to each other. The first chapter of this dissertation seeks to understand how states develop and implement their municipal stormwater programs. The second chapter of this dissertation is focused on second-order federalism questions pertaining to stormwater management. The final chapter of this dissertation provides an assessment of public participation in the stormwater program. Through these three separate, yet interrelated chapters this dissertation has several key findings. First, the way in which federal stormwater regulations are written provides great discretion to the states in developing and implementing their stormwater permits; ultimately resulting in variation across states in what is required for stormwater permittees to meet standards. Second, local governments required to obtain coverage for their stormwater discharges vary greatly in the ways in which they meet permit requirements and if they are able exceed the minimum required by state-wide general permits. Third, despite public participation efforts ranging from informing the public of the actions local governments are taking to reduce stormwater pollution, to the citizens being directly involved in decision-making processes; these forms of participation are primarily considered to be conventional methods of citizen participation. Finally, across the cases, determining effectiveness of the municipal stormwater program is based on perceptions of effectiveness, rather than how effective the program actually is in reducing polluted stormwater runoff. The combined findings from these chapters add to scholarship and provide useful information for practitioners involved in this program in several ways. First, each chapter fills gaps and extends our knowledge of the existing literature, contributing to theory building and theory expansion for the respective literature being utilized. Next, by providing information about how phase II of the municipal stormwater program works across various states and different levels of government, this dissertation provides important insights to practitioners tasked with managing stormwater for both environmental and emergency management needs. In sum, this project has both theoretical and practical significance important to the study of environmental management as well as the field of Public Administration.
Keywords: intergovernmental relations; stormwater management; public participation; implementation